Evaluation of the influence of an embedded porous silicon layer on the bulk lifetime of epitaxial layers and the interface recombination at the epitaxial layer/porous silicon interface. (15th February 2013) - Radhakrishnan, Hariharsudan Sivaramakrishnan; Dross, Frederic; Debucquoy, Maarten; Rosenits, Philipp; Van Nieuwenhuysen, Kris; Gordon, Ivan; Poortmans, Jef; Mertens, Robert
ABSTRACT Porous silicon plays an important role in the concept of wafer‐equivalent epitaxial thin‐film solar cells. Although porous silicon is beneficial in terms of long‐wavelength optical confinement and gettering of metals, it could adversely affect the quality of the epitaxial silicon layer grown on top of it by introducing additional crystal defects such as stacking faults and dislocations. Furthermore, the epitaxial layer/porous silicon interface is highly recombinative because it has a large internal surface area that is not accessible for passivation. In this work, photoluminescence is used to extract the bulk lifetime of boron‐doped (1016/cm3) epitaxial layers grown on reorganised porous silicon as well as on pristine mono‐crystalline, Czochralski, p+ silicon. Surprisingly, the bulk lifetime of epitaxial layers on top of reorganised porous silicon is found to be higher (~100–115 µs) than that of layers on top of bare p+ substrate (32–50 µs). It is believed that proper surface closure prior to epitaxial growth and metal gettering effects of porous silicon play a role in ensuring a higher lifetime. Furthermore, the epitaxial layer/porous silicon interface was found to be ~250 times more recombinative than an epitaxial layer/p+ substrate interface (S ≅ 103 cm/s). However, the inclusion of an epitaxially grown back surface field on top of the porous silicon effectively shields minority carriers from this highly recombinative interface. Copyright © 2013 John Wiley & Sons, Ltd.